Framework for Implementing Intelligence in Embedded Controls - Commuri, S. (2007)
This paper presents a framework for the realization of intelligent embedded systems for control applications. Requirements on system intelligence are translated into requirements on the system hardware and software. The hardware and software components of the design and their impact on system performance are discussed. Software and hardware architectures are presented that enable the realization of these requirements. Recent trends in the hardware-software co-design and hardware reconfigur-ation are utilized to design systems that are fault-tolerant and have higher reliability under all operating conditions. The design approach is validated by means of a case study.